Proceedings of ... annual meeting (USAIN State and Local Literature Preservation Project. Wisconsin., 1902)
Report for 1917 (17th) not issued; issued instead and included in its place: Proceedings of the National Creamery Buttermakers' Association, 20th convention (27th year), held at Milwaukee, Wisconsin, October 9-10-11, 1917.